2015
DOI: 10.1074/jbc.m115.653741
|View full text |Cite
|
Sign up to set email alerts
|

Rescue and Stabilization of Acetylcholinesterase in Skeletal Muscle by N-terminal Peptides Derived from the Noncatalytic Subunits

Abstract: Background: Most newly synthesized acetylcholinesterase molecules are catalytically inactive and rapidly degraded intracellularly; how this is regulated is not known. Results: The enzyme is stabilized by noncatalytic subunit-derived peptides and is rescued from ERAD degradation. Conclusion: Binding to noncatalytic subunits stabilizes and prevents degradation of acetylcholinesterase in skeletal muscle. Significance: Peptides that stabilize target proteins can potentially be used to increase their expression in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(11 reference statements)
1
3
0
Order By: Relevance
“…The polyproline-rich peptides in wild-type human BChE range in size from 21 to 32 residues [ 4 , 5 ] and derive from lamellipodin (Q70E73; RAPH1 gene). Studies with recombinant human BChE have demonstrated that BChE monomers can assemble into tetramers by addition of either short polyproline peptides (17–50 Pro residues) or long polyproline peptides with an average mass of 30,000 Da [ 6 ], in agreement with initial observations with recombinant AChE [ 7 , 8 ] and confirmed in skeletal muscle AChE [ 9 ].…”
Section: Introductionsupporting
confidence: 79%
“…The polyproline-rich peptides in wild-type human BChE range in size from 21 to 32 residues [ 4 , 5 ] and derive from lamellipodin (Q70E73; RAPH1 gene). Studies with recombinant human BChE have demonstrated that BChE monomers can assemble into tetramers by addition of either short polyproline peptides (17–50 Pro residues) or long polyproline peptides with an average mass of 30,000 Da [ 6 ], in agreement with initial observations with recombinant AChE [ 7 , 8 ] and confirmed in skeletal muscle AChE [ 9 ].…”
Section: Introductionsupporting
confidence: 79%
“…) and there is now clear evidence that the AChE molecules in this pool can at least in part be rescued and rerouted to the cell surface in culture and to the synapses in vivo (Ruiz et al . , and unpublished observations).…”
Section: Early Events In the Biogenesis Of Achementioning
confidence: 55%
“…These studies also suggest a therapeutic application of the PRAD peptides since a synthetic PRAD‐KDEL peptide can be taken up by cells where it rescues the inactive AChE from degradation (Ruiz et al . ). This ability to increase AChE could be useful in the treatment of patients suffering from nerve agent or pesticide exposure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation